(untitled) (Herley, PA, 2004)
This book introduces the inter-organizational information system for managing inter-organizational activities of virtual organizations, extended enterprises, and trans-enterprise systems. This book begins with the introduction to IOIS which provide readers with a bird's-eye view with extensive bibliographies including definitions, concepts, incentives for IOIS development, managerial and technological issues, etc. This is a collection of more than a dozen of contributed chapters by well-known authors from North America, Asia, Australia, and Europe. The main focus of this book is to introduce the fundamental concept and technologies of IOIS, a review and analysis of empirical research on IOIS adoption and diffusion, a new method for IOIS research, providing empirical evidence on how information systems encourage the creation of strategic networks, inter-organizational information sharing systems/decision support systems, and evaluation of IOIS.
Keywords: Business enterprises,Information resource management,Business information services; Computer network resources